ACE INHIBITORS IN PATIENTS WITH ISCHEMIC HEART DISEASE WITHOUT HEART FAILURE: CLASS EFFECTS AND EFFICACY OF ITS REPRESENTATIVES - Y. A. Karpov (Рациональная фармакотерапия в кардиологии)
Results of large-scale studies (QUIET, HOPE, EUROPA, PEACE, CAMELOT), devoted to assessment of the role of ACE inhibitors in treatment of patients with stable form of ischemic heart disease without heart failure are analyzed. Different efficacy of the representatives of this class toward risks of coronary events development and cerebral-vascular complications is shown, as well as the overall mortality risk due to cardiovascular reasons. Favorable therapeutic effects of inhibiting RAS activity in patients without left ventricle dysfunction are demonstrated in studies EUROPA with perindopril 8 mg, and HOPE with ramipril 10 mg. That became the ground of inclusion of these drugs into recommendations for treatment of all patients with ischemic heart disease after myocardial infarction, in addition to antiplatelet, lipid reducing remedies and beta-blockers.